Uma análise da experiência do fazer jornalístico e sua reconfiguração diante das mudanças tecnológicas - NASCIMENTO, Valéria dos Santos (Universidade Federal do Pará, 2022)
This research seeks to understand the journalistic work, from the perspective of those who deal with the professional activity affected by the accelerated process of communication technology. Our reflection takes place through a hermeneutic approach to the phenomenon of media communication, which involves journalistic activity, interpreted under the thought of the philosopher Martin Heidegger, in his existential analysis of Dasein, the Being-there that is inevitably a Mitsein, the Being-with -others and the matter of technique. We also added authors such as Muniz Sodré (2015), Fábio Castro (2013, 2015, 2016, 2017), José Salomão D. Amorim (2012), among others. The central objective is to reflect on contemporary journalistic practice, based on the journalists' understanding of practices, in order to understand how they make possible both the social legacy of the profession - the right to information - and the service to the new consumption habits of news due to the spread of the use of digital technologies. As a methodology for the proposed discussion, we used participant observation and interviews with professionals who work for the printed newspaper O Liberal and the portal OLiberal.com, in Belém, between 2019 and 2020. The information and data collected are exposed based on the professionals' findings and how they develop paths for action, confronting empirical and theory. In advance, it is possible to argue that there are journalisms in progress, yes, in the plural, since the profession, depending on the resources invested by companies and editorial guidelines, has different practices nowadays. In the case of this research, the observed practice reconfigures the routine established until then, impacting, to a large extent, on the journalist's own ability to maintain classic precepts of the profession, in the face of the pressures of unbridled market competition.